A falusi települések lakossági infrastruktúrájának elemzése Borsod-Abaúj-Zemplén megyében - Sikos T., Tamás (Tér és Társadalom, 1987)
During the part fourty years of socialism in Hungary, the country’s national economy has undergone significant socío-economic transformations. In the present stage of development it is a major task of the social policy and the society to réveal the inequalities in the development of individual regions and in the living standard of the urban and rural population. The development of infrastructure and settlement network is given a special attention in the present regional policy. The inadequate development of communal and social infrastructure of rural settlements and their weak communication connections lead to undesirable phenomena such as population out-migration, demographic deformation, lack of agricultural manpower, and the emergence of depression zones. The basic aim of the present paper is to reveal regional differencés in the level of communal and social infrastructure of the rural settlements within Borsod-Abaúj-Zemplén county. This county has been chosen as a model region for the following purposes: Between 1979 and 1981, P. Beluszky, together with the author, elaborated a typology of Hungarian rural settlements. It has been established that almost all types of Hungarian villages can be found in Borsod county. communal and social infrastructure is one of the most important elements in the development of rural settlements therefore it seemed to be proper to select Borsod-Abaúj-Zemplén county for the typology. In the framework of the topic chosen, the following tasks were solved: (1) A typology of rural settlements in Borsod-Abaúj-Zemplén county was prepared according to a new methodology which differs from earlier ones in the composition of indices and the mathematical-statistical methods applied; (2) A typology of community infrastructure (education, culture, transportation and housing) was elaborated with the aid of factor- and cluster analyses; (3) An information data bank was established to describe the communal and social infrastructure of rural settlements in Borsod county; (4) Functional relationships were expfored between the rural population and the various indices relating to the development of communal and social infrastructure; (5) It was determined, on the basis of factor analysis, which factors and to what extent contribute to the development and formation of community infrastructure of rural settlements in Borsod county; (6) A typology of community infrastructure of rural settlements in Borsod county was elaborated using cluster analysis. As a result of the research, the following can be established for the 352 villages of Borsod county: The community infrastructure ís in its initial stage of development in more than 40 percent of the settlements investigated. The community infrastructure is poorly developed in about 40 percent of the villages where the public utility network is mediocre. Only 17 percent of the settlements have fair or developed community infrastructure and 10 settlements (less than 3 percent) develop dynamically. These are the only ones which have an urbanlike infrastructure, similar to that in small towns. The significant role of transportation network ín the infrastructure development of rural settlements has been pointed out. The careful analysis of a map series representing the regfonal variations in the development of infrastructure, by its major types and their components, provides an opportunity for identifying those regions where there is a concentration of rural settlements with poor or underdeveloped services. These settlements are in large numbers in the Cserehát, Észak-Borsodi-Karszt, Zempléni-hegység, Hegyköz, Bodrogköz, Bükk-hegység and Borsodi Mezőség. The methodological value of the research appeared in revealing the contents of the rotated factors and in defining those factors which play a decisive role in the formation of infrastructure development: F1= the development tevel of basic services; F2= the dynamism of housing construction and amenities of dwellings; F3= the factor of unfavourable conditions in housing and communal services. The investigations carried out in Borsod county as a model region corroborated the applicability of factor- and cluster analyses in preparing a typology of community infrastructure for other counties as well as for the whole of Hungary if the databank is somewhat medified.